BICHORDITES MONASTIRIENSIS ICHNOFABRIC FROM THE PLEISTOCENE SHALLOW-MARINE SANDSTONES AT LE CASTELLA (CROTONE), IONIAN CALABRIA, SOUTHERN ITALY (Rivista italiana di Paleontologia e Stratigrafia, 2015)
The analysis of Bichordites ichnofabric has been performed in laminated calcarenites of Upper Pleistocene marine terraces of the Crotone Peninsula, Ionian Calabria, outcropping in the coast nearby the village of Le Castella (southern Italy). These calcarenitic deposits show an intense and pervasive bioturbation, preserved mainly as endichnia s.s., exposed endichnia (false epichnia with hyp- and epireliefs) and crossichnia, dominated by Bichordites monastiriensis. Other forms (more rare) are Cardioichnus isp., Ophiomorpha nodosa, Planolites beverleyensis and ?Macaronichnus-like trace fossils. This shallow-water ichnofabric, that is recurrent in many sandy shallow water marine terraces of Pleistocene, exhibits hundreds of Bichordites monastiriensis (meniscate burrows) that are studied in cross sections and plane views. A detailed taphonomic study shows many differences in the central core of Bichordites monastiriensis that varies in shape, length and dimension, from the outer meniscate envelopment, following the burrowing action of spatangoid echinids in sandy substrate. The rhythmical arrangement in shape and density of Bichordites in foreshore sandy bars with megaripples, with a regressive trend in the stratigraphic section, likely reflects variations and the strength of current along coast.